2022
DOI: 10.1371/journal.pone.0279913
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac strain is lower among women with HIV in relation to monocyte activation

Abstract: Background Women with HIV (WWH) face heightened risks of heart failure; however, insights on immune/inflammatory pathways potentially contributing to left ventricular (LV) systolic dysfunction among WWH remain limited. Setting Massachusetts General Hospital, Boston, Massachusetts. Methods Global longitudinal strain (GLS) is a sensitive measure of LV systolic function, with lower cardiac strain predicting incident heart failure and adverse heart failure outcomes. We analyzed relationships between GLS (cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Hopkins et al analysis [55] revealed a persistent elevation of monocytes levels following SARS-CoV-2 infection, attributed to classical monocytes. Additionally, Toribio et al [56] presented a correlation between myocardial performance and peripheral blood monocytes' activation in active viral infection. The comprehensive response of immunological system, secondary to vaccination, includes monocytes and antigen presentation T cells' activation.…”
Section: Discussionmentioning
confidence: 99%
“…Hopkins et al analysis [55] revealed a persistent elevation of monocytes levels following SARS-CoV-2 infection, attributed to classical monocytes. Additionally, Toribio et al [56] presented a correlation between myocardial performance and peripheral blood monocytes' activation in active viral infection. The comprehensive response of immunological system, secondary to vaccination, includes monocytes and antigen presentation T cells' activation.…”
Section: Discussionmentioning
confidence: 99%